Strategy of Rice Variety Technology Transfer for Supporting the Agricultural Inventions Commercialization - Morina Pasaribu; Lukman M. Baga; Joko Purwono (Jurnal Penelitian Pertanian Terapan, 2021)
Innovation is an important aspect in the nation's competitiveness. Technology transfer is required to bring invention into innovation. However, the implementation technology transfer, especially commercialization technology is still considerably low. This challenge is faced by Indonesian Agency for Agricultural Research and Development (IAARD) to commercialize Indonesian rice varieties. Adoption and interest of Industry in the commercialization of varieties invented by IAARD in 2019 was only 11%. This study aims to build roadmap business strategy for commercialization rice varieties invented by IAARD. The method used in this research was a business model canvas approach, SWOT analysis, and a strategic roadmap. The results showed that there were 11 strategies that can be applied in four approaches , namely a) intensive strategy: expanding and mapping new customer segmentation, optimizing promotion mechanisms and attracting new partners, and strengthening the organizational structure of implementing technology transfer, b) turn-around strategy: adding and increasing HR competence, planning R&D activities by measuring Technology Readiness Level (TRL or TKT), and increasing the capacity of facilities and infrastructure, c) diversification strategy: improving the quality of rice varieties and commercial technology transfer services, pre-licensing, and d) consolidation strategy: building information systems, collaborative alliances with stakeholders, and valuation of intangible assets. The strategies were described in 19 programs mapped on a strategy roadmap of transfer of technology on commercialization rice variety invented by IAARD.